Chironomids (Diptera) from Central European stream networks: new findings and taxonomic issues - Bernadett Boóz; Zsolt Kovács; Bea Bartalovics; Pál Boda; Marko Miliša; Bálint Pernecker; Petr Pařil; Tomasz Rewicz; Anna Boglárka Simon; Zoltán Csabai; Arnold Móra (Biodiversity Data Journal)
Chironomidae, with over 7,300 described species, are amongst the most diverse and abundant insect families in freshwater ecosystems worldwide. Chironomids are known for their widespread distribution from various water types. The level of documentation of chironomid fauna varies considerably amongst European countries, with more comprehensive knowledge for Western Europe compared to other regions. Despite the recent extensive sampling effort and the increasing number of available data, the chironomid fauna of Central European countries still remains poorly known.This study contributes to the knowledge of chironomid fauna in three river catchments in Croatia, Hungary and Czechia. A combination of morphological and molecular techniques was employed, with a focus on larvae, although pupae and exuviae were also examined. We found 207 taxa, amongst which 170 were identified to species level. In Croatia, 14 species were recorded for the first time and two species were newly recorded in Czechia. DNA barcoding of 31 specimens resulted in 23 BINs, including eight new ones to BOLD. We provided detailed notes on taxa with taxonomic problems and/or morphological peculiarities. Our results highlight that extensive studies conducted in relatively small areas and a limited range of habitats (only streams in hilly regions) can remarkably contribute to the local and global knowledge on Chironomidae fauna, especially when the taxonomically difficult and often problematic larvae are investigated.